Never wager with a wallflower eaudiobook A novel. - Heath, Virginia (The Merriwell Sisters, 2023)
Never Wager with a Wallflower is the third and final delightful installment in the Merriwell Sister's Regency rom-com series. Miss Venus Merriwell has been waiting for her prince to come since the tender age of fourteen. She wants a man who is selfless, academic like her, and free from all the wretched vices her gambler father enjoyed far too much before he left the Merriwell sisters practically destitute. Unfortunately, after a slew of romantic disappointments, there is still no sign of that prince at twenty-three and the only one true love of her life is the bursting-at-the-seams orphanage in Covent Garden that she works tirelessly for. An orphanage that desperately needs to expand into the empty building next door. For Galahad Sinclair, gambling isn’t just his life, it’s in his blood. He grew up and learned the trade at his grandfather’s knee in a tavern on the far away banks of the Hudson in New York. But when fate took all that away and dragged him across the sea to London, it made sense to set up shop here. He’s spent five years making a success out of his gaming hell in the sleazy docks of the East End. Enough that he can finally afford to buy the pleasure palace of his dreams—and where better than in the capital’s sinful heart, Covent Garden? The only fly in his ointment is the perfect building he’s just bought to put it in also happens to be right next door to the orphanage run by his cousin’s wife’s youngest sister. A pious, disapproving and unsettling siren he has avoided like the plague since she flattened him five years ago… While Venus and Galahad lock horns over practically everything, and while her malevolent orphans do their darndest to sabotage his lifelong dream, can either of them take the ultimate gamble—and learn to love thy neighbor?